Povidone iodine skin absorption: An ex-vivo study. Issue 3 (15th June 2015) - Nesvadbova, Martina; Crosera, Matteo; Maina, Giovanni; Larese Filon, Francesca
Highlights: Povidone iodine hand-scrub solutions, which are considered safe antiseptics, contain large amounts of iodine that can be absorbed by skin. Iodine can be absorbed through intact skin in time dependent manner. In professional use the repetitive contact with PI, also as soap, can cause iodine skin permeation that must be considered when the washing procedures are repeated more than 20 times a day. Abstract: Povidone iodine is a water-soluble complex used to disinfect the skin surface and it exerts prolonged germicidal action against a broad spectrum of germs. Indeed, it is often applied on burned skin, large wounds, deep tissues or mucosa. Notably some surgical hand-scrub solutions, which are considered safe antiseptics, contain large amounts of iodine that can be absorbed by skin. The aim of present study was to study the skin absorption of iodine after the application on the skin of povidone-iodine solution, used by health care workers during surgical procedure. We use Franz diffusion static cells with human skin. After 24 h from the beginning of our measurement the iodine concentration in the receiving compartment was 11.59 ± 6.3 μg/cm 2 . The medium flux calculated was 0.73 ± 0.33 μg/cm 2 /h with a lag time of 8.9 ± 1.5 h. These in vitro results confirmed that povidone iodine could pass through the skin in a relevant amount that can explain the clinical findings in burned or surgically treated patients. In professional use the repetitive contact with povidone iodine, also as soap, can cause iodine skin permeation that must be considered when the washing procedures are repeated more than 20 times a day.